PERBEDAAN PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN DISPOSISI MATEMATIS MELALUI PENDEKATAN MATEMATIKA REALISTIS DAN INKUIRI SISWA SD - Ani Harun (JURNAL TEMATIK, 2019)
This research aims to knows: (1) difference improving the problem solving ability of Mathematical and disposition by using Realistic Mathematical approach and Inquiry Learning approach, (2) the process of student answers in solving problems related to problem solving skills and mathematical disposition through the approach of Realistic Mathematics and Inquiry Approach. The population of this research is all students of grade VI Public Elementary School 053984 Hinai Kanan District Langkat. The sample in this research was taken by purposive sampling. The sample of this research totals 50 students consisting of two classes i.e. VI-A and VI-B. Class VI-A as experimental class I and class VI-B as a experimental class II with 25 students each. The design used in this research is quasi experiment. The instrument used in this research is the test of mathematical solving ability and disposition. Analysis of data used T-Test assisted application SPSS 18.0 for windows. The results showed: (1) there is an increasing difference between the mathematical solving abilities taught by Realistic Mathematical and Inquiry Learning approach. (2) the process of student answers taught with Realistic Mathematics Approach is better than the process of student answers given through the Inquiry Learning approach.